KARAKTERISTIK KONSUMEN DALAM PEMBELIAN DAGING SAPI DI KOTA MANADO (STUDI KASUS DI TRANSMART CARREFOUR STAR SQUARE MANADO) - Mongi, Anastasia I; Wantasen, E; Salendu, A H.S; Manese, M (ZOOTEC, 2019)
CONSUMERS CHARACTERISTICS IN PURCHASING BEEF IN MANADO CITY (Case Study On Transmart Carrefour Star Square Manado).Beef is one of the products farm source of protein easily found in the modern market and traditional markets. Consumer behavior is the study of decision making.Consumer characteristics are part of consumer behavior so companies that sell products need to recognize consumer characteristics and decision models made by consumers and innovate on beef attributes so that they can attract consumers to buy. Respondents in this stady were 100 determined by the probability of sampling non next using descriptive analysis through the questionnaire to know the types of buyers. The results showed that the types of buyers of beef in transmart Carrefour star square manado dominated by consumers women are mostly housewives with average ages of more than 40 years, monthly income on 3 million with the education level medium to collage.Keywords : Beef, consumer characteristics, beef attribute